2016
DOI: 10.1002/pat.3902
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, mechanical, optical and thermal properties of PVC/ZnO‐EDTA nanocomposite films

Abstract: Covalent surface functionalization of synthesized ZnO nanoparticles (NP)s with ethylenediaminetetraacetic acid (EDTA) was successfully carried out. Modified ZnO‐EDTA NPs as a viable and inexpensive filler were incorporated into poly(vinyl chloride) PVC matrix after their chemical modification to investigate the agglomeration behavior. All prepared materials including modified NPs and PVC/ZnO‐EDTA nanocomposites (NC)s were analyzed by Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the literature, it was reported that when ZnO was added to PVC, UV absorption increased and transmittance was decreased [7,8]. Optical reflectance and transmittance plots of nanofibers produced in this study were demonstrated in Figure 8.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In the literature, it was reported that when ZnO was added to PVC, UV absorption increased and transmittance was decreased [7,8]. Optical reflectance and transmittance plots of nanofibers produced in this study were demonstrated in Figure 8.…”
Section: Resultsmentioning
confidence: 60%
“…Since corresponding ZnO peaks are not presented at the XRD patterns [18,19], it is very difficult to mention that zinc nitrate was transformed to well crystallize zinc oxide structure in this study. In the literature, it was reported that when ZnO was added to PVC, UV absorption increased and transmittance was decreased [7,8]. Optical reflectance and transmittance plots of nanofibers produced in this study were demonstrated in Figure 8.…”
Section: Sayfa 121mentioning
confidence: 60%
See 1 more Smart Citation
“…A variety of polymeric matrices, ranging from polyolefins to polyesters, polyurethanes and silicon polymers, together with other materials including glass, titania or nanofibers 11–14 have been investigated for the production of antimicrobial materials. In particular, polyvinyl chloride (PVC) is a versatile polymer widely used for the production of medical devices as well as enteral feeding products and novel materials with antimicrobial activity have been obtained by incorporation of metal oxides, nanoparticles and zeolites, ionic liquids and natural substances into this polymer matrix 15–20 …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, surface modification of NPs with coupling agents and stabilizers (eg, organic compounds, polymer, proteins etc.) or charging the NP surface to isolate them by electrostatic repulsion was adopted to avoid aggregation …”
Section: Introductionmentioning
confidence: 99%